Introduction of a web portal for an Individual Health Management and observational health data sciences - Melchart D; Eustachi A; Gronwald S; Wühr E; Wifling K; Bachmeier BE (Patient Related Outcome Measures, 2018)
Dieter Melchart,1,2 Axel Eustachi,1 Stephan Gronwald,3 Erich Wühr,3 Kristina Wifling,1 Beatrice E Bachmeier1,4 1Competence Centre for Complementary Medicine and Naturopathy, Klinikum Rechts der Isar, Technische Universität München, Munich, Germany; 2Institute for Complementary and Integrative Medicine, University Hospital Zurich and University of Zurich, Zurich, Switzerland; 3Applied Health Care Science, Deggendorf Institute of Technology, Deggendorf, Germany; 4Institute of Laboratory Medicine, Ludwig-Maximilians-University, Munich, Germany Background: There is a global trend to a stronger active involvement of persons in the maintenance and restoring of health. The Competence Centre for Complementary Medicine and Naturopathy (CoCoNat) of the Technical University of Munich (TUM) has developed a lifestyle concept to enable each individual to manage his or her health – Individual Health Management (IHM) – and a web-based health portal named Virtual Tool for Education, Reporting, Information and Outcomes (VITERIO®), which addresses these needs for practice and research. Objectives: The objectives of this study were to establish a core set of questionnaires for a self-assessment program on certain risk indications and comprehensive protection factors of health and to develop and enhance 1) tools for individual feedback, longitudinal self-monitoring, self-assessment, and (self-)care-planning; 2) training packages; 3) open notes and records for provider and patient; and 4) tools for monitoring groups and single participants in various indicators for individual coaching and scientific evaluation. Methods: The CoCoNat of TUM, Faculty for Applied Health Science of Technische Hochschule Deggendorf, VITERIO® company, IHM campus network, and Erich Rothenfußer Foundation, Munich, provide a consortium responsible for content, research strategy, technical production and implication, postgraduate education for IHM coaches, implementation of IHM in various settings, and funding resources. Results: A data set of indicators for health screening and self-monitoring of findings, symptoms, health behavior, and attitudes are integrated into a web-based health portal named VITERIO®. The article introduces some implemented graphical solutions of developed tools and gives examples for daily use. Conclusion: Behavioral change and adaptation in attitudes and personal values are difficult issues of health education and lifestyle medicine. To address this problem best, the implementation of a patient-centric, performance measures-based program including open records and a blended learning concept were elaborated. The combination of an individual web-based health portal with personal coaching allows the implementation of IHM in everyday practice. Keywords: lifestyle program, Individual Health Management, IHM, blended learning, performance measures, web-based health portal, adherence